The Role of Self-Efficacy in Students of Al-Muhsin Islamic Boarding School Yogyakarta in Memorizing the Qur'an - Fauziah, Kuni Isna Ariesta (Journal of Education and Learning Sciences, 2025)
Students have the main task of studying and fully participating in academic and non-academic campus activities. Memorizing the Qur'an / tahfidz al-Qur'an is the process of inserting the verses of the Qur'an into the heart and mind so that they are not lost. In memorizing the Qur'an, not all memorization has the same capacity, namely being able to memorize easily and quickly. Of course, there are ways / methods for each in achieving memorization. In this case, tahfidz students or memorizers of the Qur'an who are in Islamic boarding schools have a double task, first: studying campus courses, second: memorizing the verses of the Qur'an. Self-efficacy in memorizing the Qur'an is an individual's belief in the ability to achieve goals and the ability to overcome problems or obstacles to memorizing the Qur'an. This study aims to determine the role of self-efficacy in students in memorizing the Qur'an. The research method used is a qualitative descriptive method, through observation and interview techniques. The conclusion of this study shows that self-efficacy affects memorization of the Qur'an in students. Memorizing the Qur'an will be achieved well through: first, individuals have self-enthusiasts so that they form behavior in completing memorization tasks. Second, individuals say they are unable due to lack of experience in successfully achieving the target of memorizing the Qur'an. In addition, the results of this study still have a gap with the theory that high self-efficacy guarantees successful memorization. While the level of memorization success is also determined by internal and external conditions.